Rural Livelihoods, Resources and Coping with Crisis in Indonesia A Comparative Study - Burgers, Paul P.M; Titus, Milan J. (ICAS Publications Series / Edited Volumes, 2009)
Most literature on the economic crisis in indonesia has focused on the negative macro-economic impacts during the "crisis- years" of 1997-99. The case studies presented in this book take a different perspective. With a longitudinal research perspective, this comparative study analyses a wide variety of responses to the crisis among communities and households. The case studies in this book cover the coping and adapting mechanisms of rural households under a variety of resource use practices and resource use regulations in different areas of Indonesia.